Incidental giant thymoma—a reminder of the importance of a global look of the imaging scans. Issue 3 (4th March 2023) - Policarpo, Filipa; Antunes, Mariana; Alvoeiro, Magda; Alvoeiro, Francisco
Abstract: A 49-year-old female patient, without previous medical history, underwent a thoracic CT due to SARS-CoV2 infection. This exam revealed a heterogeneous mass in the anterior mediastinum with 11 × 8.8 cm in close contact with main thoracic vessels and pericardium. Surgical biopsy documented a B2 thymoma. This clinical case reminds the importance of a systematic and global look of the imaging scans. Years before the thymoma diagnosis, the patient underwent a shoulder X-ray due to musculoskeletal pain, where an irregular shape of the aortic arch was visible, probably related to the growing mediastinal mass. An earlier diagnosis would allow a complete mass resection without such extensive surgery and less morbidity.